2022
DOI: 10.3389/fpsyg.2022.919157
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the Fourth Industrial Revolution on organisational culture: An empirical investigation

Abstract: The Fourth Industrial Revolution (4IR) is known to transform and create opportunities for the world of work. However, little is known about how the future workforce, such as university students, are being equipped and exposed to 4IR technologies and ways of thinking in a South African (SA) context. This study’s findings contribute to understanding the influence of organisational culture on the uptake of 4IR technology within higher education (HE) in SA during a pandemic. The study uses Edgar Schein’s theoretic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Employees need support in dealing with the 4IR and developing their skills, according to industrial and organisational psychologists (Ghislieri et al, 2018). Singaram and Mayer (2022), coming from the same disciplinary field, have pointed out that the skill development of employees needs an ambitious and competitive organisational culture, which incorporates 4IR thinking, policymaking and motivation in leaders of organisations, while taking the broader societal contexts of the organisations into consideration. Previous studies have, at the same time, shown that organisations that invest in the development of their employees experience major losses because employees do not transfer the new skills and competences into their workplaces (Caravella & Menghini, 2018;Makridakis, 2017;Park, 2017).…”
Section: Skill Development In the Fourth Industrial Revolutionmentioning
confidence: 99%
“…Employees need support in dealing with the 4IR and developing their skills, according to industrial and organisational psychologists (Ghislieri et al, 2018). Singaram and Mayer (2022), coming from the same disciplinary field, have pointed out that the skill development of employees needs an ambitious and competitive organisational culture, which incorporates 4IR thinking, policymaking and motivation in leaders of organisations, while taking the broader societal contexts of the organisations into consideration. Previous studies have, at the same time, shown that organisations that invest in the development of their employees experience major losses because employees do not transfer the new skills and competences into their workplaces (Caravella & Menghini, 2018;Makridakis, 2017;Park, 2017).…”
Section: Skill Development In the Fourth Industrial Revolutionmentioning
confidence: 99%
“…The study by Gan and Balakrishnan (2017) further corroborates that computer self-efficacy moderately predicts behavioral intention in the context of mobile technology adoption. In the educational domain, existing literature (Alqurashi, 2016;Chester et al, 2011;Domenech-Betoret et al, 2017;Hillier et al, 2013;Schunk, 1985;Shank and Cotten, 2014;Valencia-Vallejo et al, 2016) consistently demonstrates the positive impact of computer self-efficacy on students' acceptance of technology for learning purposes.…”
Section: Literature Reviewmentioning
confidence: 99%